GEOMORPHOLOGICAL AND MORPHOTECTONIC ANALYSIS OF MALAKASIOTIS DRAINAGE BASIN (WEST THESSALY-TRIKALA PREFECTURE - ΜΠΑΘΡΕΛΛΟΣ Γ.; ΣΚΥΛΟΔΗΜΟΥ Χ.; ΛΕΙΒΑΔΙΤΗΣ Γ.; ΒΕΡΥΚΙΟΥ- ΠΑΠΑΣΠΥΡΙΔΑΚΟΥ Ε. (Bulletin of the Geological Society of Greece, 2005)
The Malakasiotiko stream is one of the tributaries of Pinios River in Western Thessaly. The drainage basin of Malakasiotiko stream is located in the northwestern part of the mountainous zone of Trikala Prefecture. In this paper, the drainage network of Malakasiotiko stream has been analyzed. Additionally, the relationship among the tectonism, the growth directions of the watershed lines, and the drainage network. The quantitative analysis of the drainage network has resulted that the geological and tectonic structure of the area affected, and potentially has been affecting its development. The morphotectonic analysis has shown that the watershed lines of the drainage basin and the streams of 1st to 4th order are influenced by alpine structure, whereas the 5th, 6th and the 7th order streams are influenced by neotectonic activity.